Performance Efficiency Of Zakat Management Organization (OPZ) In Indonesia - Wijayanti, Intan Manggala; Ibrahim, Mohamad Andri; Fauziah, Eva; Gustriana, Dina; Az-zahra, Nadya (LAA MAISYIR : Jurnal Ekonomi Islam, 2021)
This study aims to measure the efficiency level of OPZ performance in Indonesia from 2017 to 2019 period. This study employed non-parametric quantitative methods, and the technique of data collection was documentation which was collected from secondary data, including annual financial reports of BAZNAS, Rumah Zakat, Dompet Dhuafa, ACT, and PKPU for the period 2017-2019. There were two variables i.e. input and output variables. The input variable consists of total assets and operational costs, while the output variable is the receipt and the distribution of zakat funds. According to the analysis result using DEA method, it shows that the institutions with efficiency levels of 100% in 2017 were ACT, BAZNAS, and Dompet Dhuafa; Dompet Dhuafa and Rumah Zakat in 2018; and in 2019 were BAZNAS and Rumah Zakat. In 2018 and 2019, the efficiency values of ACT were relatively declined, while from 2017 to 2020 PKPU did not reach 100% or inefficiency. Inefficiency can be handled by setting targets according to the amount specified in the calculation of DEA scale efficiency.